Statewide Programs for Administrator Training and Development: The Oregon Leadership Academy for School Administrators - Kate Dickson (Educational Considerations, 1989)
Approximately 40 percent of the states have selected a comprehensive statewide LEAD program. (Program Approaches to Administrative Training and Development.)